Effects of Inspiratory Muscles Trainer in Pulmonary Rehabilitation Program among COPD Patients - Rabiya Noor, Wajeeha Zia, Mashar Hayyat, Iqra Ishriaq, Alveena Shakoor, Mehwish Khalid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic obstructive pulmonary disease (COPD) is associated with prolonged respiratory problems and compromised airflow. Eventually, routine activities become troublesome. Pulmonary rehabilitation program and specific training of inspiratory muscles can do management of such patients. Aim: To find out the effects of Inspiratory Muscle Trainer on dyspnea in moderate COPD patients during Pulmonary Rehabilitation in terms of improvement of pulmonary lung function and Multidimensional Dyspnea profile. Study Design: Randomized controlled trial. Methodology: Two groups were designed; in one group Pulmonary Rehabilitation Program was applied in other group both PRP and IMT was given. Patients were recruited into two groups by simple random technique. Pre-treatment measurements were taken and then Sessions of 4 weeks with 5 days per week were given and post treatment assessment was done. Data was evaluated by using SPSS version 24. Independent sample t-test was applied to determine any significant difference between Pre-treatment and Post-treatment Functional pulmonary assessment between two groups. Results: Findings revealed that differences between two groups were statistically significant (p <0.05) and also statistically significant difference were observed within group analysis (p< 0.05) with respect to dyspnea , fatigue , quality of life. Practical Implication: This study considered moderate COPD patients for Inspiratory Muscle training (IMT) along with Multi-Disciplinary Approach in slowing down the worsening of disease and in this way prevented the future complications. Conclusion: It was concluded that inspiratory muscle trainer group was more effective as compare to standard rehabilitation in improving pulmonary function testing and reducing dyspnea among COPD patients. Keywords: Dyspnea, Inspiratory Muscle Training and Pulmonary Rehabilitation Programme.